Pedagogical Approaches to Enhancing Fine Motor Skills in Early Childhood through Play-Based Activities - Faziras Nur Amira; Rozman Ab. Kadir (International Journal of Pedagogy, 2025)
Early childhood is a critical period of rapid physical and mental development, often referred to as the "golden age" due to the significant potential for growth and learning. During this stage, it is essential to stimulate children's abilities through intentional and developmentally appropriate pedagogical practices. Fine motor development, which involves the coordination of small muscles and hand-eye coordination, plays a vital role in children's overall growth and readiness for further learning. This literature-based study explores pedagogical approaches aimed at enhancing fine motor skills in early childhood through play-based activities such as coloring, collage-making, and stringing beads. Coloring encourages children to express themselves creatively while improving their grip and precision. Collage-making fosters hand coordination and sensory exploration by assembling various materials into visual compositions. Stringing beads enhances concentration, sequencing, and finger dexterity. These activities demonstrate how play, when guided by pedagogical principles, can effectively support fine motor skill development in early learners.